Transcriptome analysis in contrasting maize inbred lines and functional analysis of five maize NAC genes under drought stress treatment - Ding, Ning; Zhao, Ying; Wang, Weixiang; Liu, Xuyang; Shi, Wentong; Zhang, Dengfeng; Chen, Jiajie; Ma, Shuo; Sun, Qingpeng; Wang, Tianyu; Lu, Min (Frontiers in Plant Science, 2023)
NAC transcription factors (TFs) have received much attention for its critical roles in drought stress responses. To explore the maize NAC genes in response to drought stress, transcriptome sequencing data of NAC TFs in two maize inbred lines, the drought tolerance line H082183 and the sensitive line Lv28, were used to screen the differentially expressed genes (DEGs). 129 maize NAC protein-coding genes were identified, of which 15 and 20 NAC genes were differential expressed between the two genotypes under MD and SD treatments, respectively. Meanwhile, phylogenetic relationship of 152 non-redundant NAC family TFs in maize were generated. The maize NAC family proteins were grouped into 13 distinct subfamilies. Five drought stress-responsive NAC family members, which were designed as ZmNAP, ZmNAC19, ZmNAC4, ZmJUB1(JUBGBRUNNEN1) and ZmNAC87 were selected for further study. The expression of ZmNAP, ZmNAC19, ZmNAC4, ZmJUB1 and ZmNAC87 were significantly induced by drought, dehydration, PEG stress and ABA treatments. The overexpressing Arabidopsis of these five NAC genes were generated for functional characterization, respectively. Under different concentrations of NaCl, D-Mannitol stress and ABA treatments, the sensitivity of ZmNAP, ZmNAC19, ZmNAC4, ZmJUB1 and ZmNAC87 overexpressing lines was significantly increased at the germination stage compared to the wild-type (WT) lines. Overexpression of these five NAC members significantly improved the drought stress tolerance in transgenic Arabidopsis. Yeast two-hybrid screening analysis revealed that ZmNAP may cooperatively interact with 11 proteins including ZmNAC19 to activate drought stress response. The above results inferred that ZmNAP, ZmNAC19, ZmNAC4, ZmJUB1 and ZmNAC87 may play important roles in plant response to drought stress, and may be useful in bioengineering breeding and drought tolerance improvement.